Proximal and time‐varying effects of cigarette, alcohol, marijuana and other hard drug use on adolescent dating aggression. Issue 3 (20th February 2014) - McNaughton Reyes, H. Luz; Foshee, Vangie A.; Bauer, Daniel J.; Ennett, Susan T.
ABSTRACT: Although numerous studies have established a link between substance use and adult partner violence, little research has examined the relationship during adolescence and most extant research has not examined multiple substance use types. The current study used hierarchical growth modeling to simultaneously examine proximal (between‐person) and time‐varying (within‐person) relations between cigarette, alcohol, marijuana and hard drug use and physical dating aggression across grades 8 through 12 while controlling for demographic covariates and shared risk factors. Proximal effects of marijuana use on dating aggression were found for girls and proximal effects of hard drug use on dating aggression were found for boys. Time‐varying effects were found for alcohol for both boys and girls and for hard drug use for boys only. Overall, findings suggest that alcohol, marijuana and hard drug use predict whether and when adolescents engage in dating aggression and should be targeted by prevention interventions.